Surface characterization of polymers by XPS and SIMS techniques - Kovač, Janez (Materiali in tehnologije, 2011)
Polymers are very often subjects of different surface treatments. To understand and control the basic processes during surfaces modifications, analyses with advanced analytical techniques are required. We present two of such state of the art techniques, X-ray photoelectron spectroscopy - XPS and secondary ion mass spectroscopy - SIMS, often applied for characterization of polymers surfaces. In this work we give an overview of these techniques and their advantages and limitations related to polymer characterization. The combined use of these techniques is demonstrated in the application example, in which the cotton fibers were characterized before and after deposition of fluorine-based thin coating.
Keywords: karakterizacija materialov; rentgenska fotoelektronska spektroskopija; spektroskopija sekundarnih ionov; polimeri; bombaž